Formal synthesis of (-)-quinagolide: diastereoselective ring expansion via a bicyclic aziridinium ion strategy to access the octahydrobenzo[g]quinoline architecture - Chavan, Subhash P.; Kawale, Sanket A.; Pisal, Mahesh M.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2021)
The diastereoselective formal synthesis of (-)-quinagolide, a D-2 receptor agonist, has been achieved. The synthesis started from L-pyroglutamic acid and relied on utilization of (a) a stereospecific catalytic hydrogenation and diastereoselective Horner-Emmons-Michael cascade to obtain functionalized prolinate, (b) a Lewis acid mediated Pummerer cyclization to construct a tricyclic fused ring system, and (c) a diastereoselective ring expansion via a bicyclic aziridinium intermediate to access the required 3-substituted piperidine scaffold.